Small-Molecule Amyloid Beta-Aggregation Inhibitors in Alzheimer's Disease Drug Development - Sharmin Reza Chowdhury; Fangzhou Xie; Jinxin Gu; Lei Fu (Georg Thieme Verlag KG, 2019)
Alzheimer's disease (AD) is still an incurable neurodegenerative disease that causes dementia. AD changes the brain function that, over time, impairs memory and diminishes judgment and reasoning ability. Pathophysiology of AD is complex. Till now the cause of AD remains unknown, but risk factors include family history and genetic predisposition. The drugs previously approved for AD treatment do not modify the disease process and only provide symptomatic improvement. Over the past few decades, research has led to significant progress in the understanding of the disease, leading to several novel strategies that may modify the disease process. One of the major developments in this direction is the amyloid β (Aβ) aggregation. Small molecules could block the initial stages of Aβ aggregation, which could be the starting point for the design and development of new AD drugs in the near future. In this review we summarize the most promising small-molecule Aβ-aggregation inhibitors including natural compounds, novel small molecules, and also those are in clinical trials. Moreover, we briefly summarized some reported docking studies of small-molecule Aβ aggregation inhibitors. These will give us an idea about the chemical features required to design novel small molecules with anti-Aβ aggregation properties.